دور الترجمة في تيسير الحوار بين الثقافات: Role of Translation in facilitating Intercultural Dialogue (Al-Qamar, 2021)
The purpose of this study is to discover the range and nature of the association between Translation and Intercultural dialogue due to growing importance of the role of translation in culture and wide interest in the relationship between translation and intercultural dialogue This study focuses on analyzing the role of translation for facilitating the intercultural dialogue by examining the relationship between translation and culture in the light of various scholars’ view point. It provides insights on the concepts of translation, its significant types including cultural translation and communicative translation revealed by various translation scholars. It also identifies the concept of intercultural dialogue, its objectives, and requirements making successful intercultural dialogue. In view of the remit of this study, the constraints and several approaches towards understanding the concept of intercultural dialogue addressed by various interculturalists were also highlighted. However, some conclusions and recommendations were mentioned by realizing that translation plays an important role in facilitating intercultural dialogue which leads to the promotion of peaceful coexistence among various societies, and it has great contributions to transfer and exchange the ideas among the followers of various cultures and helps them in creating conducive environment in a human society.
Keywords: Translation; Intercultural Dialogue; Role; Culture and Cultural Diversity